Probing the Mechanism of Allylic Substitution of Morita–Baylis–Hillman Acetates (MBHAs) by using the Silyl Phosphonite Paradigm: Scope and Applications of a Versatile Transformation. Issue 8 (9th January 2015) - Kalyva, Maria; Zografos, Alexandros L.; Kapourani, Era; Giambazolias, Evaggelos; Devel, Laurent; Papakyriakou, Athanasios; Dive, Vincent; Lazarou, Yannis G.; Georgiadis, Dimitris
Abstract A PC bond‐forming reaction between silyl phosphonites and Morita–Baylis–Hillman acetates (MBHAs) is explored as a general alternative towards medicinally relevant β‐carboxyphosphinic structural motifs. Conversion rates of diversely substituted MBHAs to phosphinic acids 9 or 14 that were recorded by using 31P NMR spectroscopy revealed unexpected reactivity differences between ester and nitrile derivatives. These kinetic profiles and DFT calculations support a mechanistic scenario in which observed differences can be explained from the "lateness" of transition states. In addition, we provide experimental evidence suggesting that enolates due to initial P‐Michael addition are not formed. Based on the proposed mechanistic scenario in conjunction with DFT calculations, an interpretation of the E/Z stereoselectivity differences between ester and nitriles is proposed. Synthetic opportunities stemming from this transformation are presented, which deal with the preparation of several synthetically capricious phosphinic building blocks, whose access through the classical P‐Michael synthetic route is not straightforward.